Reproductive Seasonality in Nesticus (Araneae: Nesticidae) Cave Spiders - Carver, Linnea M. (PLoS One, 2016)
Spiders of the family Nesticidae are members of cave communities around the world with cave-obligate (troglobiotic) species known from North America, Europe, Asia and the Indo-Pacific. A radiation of Nesticus (Araneae: Nesticidae) in the southern Appalachians includes ten troglobiotic species. Many of these species are of conservation interest due to their small ranges, with four species being single-cave endemics. Despite conservation concerns and their important role as predators in cave communities, we know little about reproduction and feeding in this group. We addressed this knowledge gap by examining populations of two species on a monthly basis for one year. We made further observations on several other species and populations, totaling 671 individual spider observations. This more than doubled the reported observations of reproduction and feeding in troglobiotic Nesticus. Female Nesticus carry egg sacs, facilitating the determination of the timing and frequency of reproduction. We found that Nesticus exhibit reproductive seasonality. Females carried egg sacs from May through October, with a peak in frequency in June. These spiders were rarely observed with prey; only 3.3% (22/671) of individuals were observed with prey items. The frequency at which prey items were observed did not vary by season. Common prey items were flies, beetles and millipedes. Troglobiotic species constituted approximately half of all prey items observed. This result represents a greater proportion of troglobiotic prey than has been reported for various troglophilic spiders. Although our findings shed light on the life history of troglobiotic Nesticus and on their role in cave ecosystems, further work is necessary to support effective conservation planning for many of these rare species.